Colombian Scholars' Discussion About Language Assessment: A Review of Five Journals - Sonia Patricia Hernandez-Ocampo (Universidad Nacional de Colombia, 2022)
The current discussion about assessment in the language teaching context-involving topics such as immigration and citizenship, and university entrance-has brought with it the issue of justice in assessment. Although in Colombia such concerns are not generally discussed, it is important to consider fairness when it comes to classroom assessment. This paper presents a review of five Colombian well-known journals during the period 2009-2020 aiming to identify the scholarly discussion regarding language assessment and testing in the country. Findings suggest that Colombian researchers are concerned with fair and democratic assessment practices, and the involvement of students in peer- and self-assessment practices to improve learning and promote autonomy. Also, there is a perceived need for more teacher education in language assessment.